2000
DOI: 10.1097/00006254-200010000-00017
|View full text |Cite
|
Sign up to set email alerts
|

Role of the cAMP Signaling Pathway in the Regulation of Gonadotropin-Releasing Hormone Secretion in GT1 Cells

Abstract: We studied the signaling pathways coupling gonadotropin-releasing hormone (GnRH) secretion to elevations in cAMP levels in the GT1 GnRH-secreting neuronal cell line. We hypothesized that increased cAMP could be acting directly by means of cyclic nucleotide-gated (CNG) cation channels or indirectly by means of activation of cAMP-dependent protein kinase (PKA). We showed that GT1 cells express the three CNG subunits present in olfactory neurons (CNG2,-4.3, and-5) and exhibit functional cAMP-gated cation channels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
18
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(25 citation statements)
references
References 23 publications
7
18
0
Order By: Relevance
“…In accordance with the former possibility, we were unable to observe any effect of charybdotoxin or iberiotoxin, two specific blockers of BK-type I KC a , on GnRH-induced electrical activity (Van Goor et al, 1999a Vitalis et al (2000) have reported recently that the olfactory subtype of CNG channels is expressed in GT1 cells. These channels have a preference for cAMP over cGMP (Wei et al, 1998) and are inhibited by [Ca 2ϩ ] i either directly (Finn et al, 1996;Wei et al, 1998) or indirectly via modulation of AC activity (Hurley, 1999).…”
Section: Resultssupporting
confidence: 82%
See 2 more Smart Citations
“…In accordance with the former possibility, we were unable to observe any effect of charybdotoxin or iberiotoxin, two specific blockers of BK-type I KC a , on GnRH-induced electrical activity (Van Goor et al, 1999a Vitalis et al (2000) have reported recently that the olfactory subtype of CNG channels is expressed in GT1 cells. These channels have a preference for cAMP over cGMP (Wei et al, 1998) and are inhibited by [Ca 2ϩ ] i either directly (Finn et al, 1996;Wei et al, 1998) or indirectly via modulation of AC activity (Hurley, 1999).…”
Section: Resultssupporting
confidence: 82%
“…Although we have not recorded I d experimentally, the CNG channel recently described by Vitalis et al (2000) in GT1 cells is an obvious candidate. Another, more complex, possibility is that I d could actually represent [Ca 2ϩ ] i -mediated inactivation of I SOC (Lewis, 1999).…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…We demonstrate that adipocyte lipase activities, specifi cally ATGL and, to a lesser extent, HSL, are involved in the regulated secretion of aP2, and genetic deletion or chemical inhibition of these enzymes dramatically diminishes aP2 secretion from adipocytes. It has been reported in various systems that cAMP signaling positively regulates classical and nonclassical hormone secretion (50)(51)(52)(53). However, induction of hormone secretion has not previously been associated with specifi c lipase activity or free fatty acid availability in adipocytes and has not been linked to aP2 secretion.…”
Section: Downloaded Frommentioning
confidence: 99%
“…In contrast, the activation of the Ca 2+ dependent phosphatase calcineurin causes dephosphorylation of the channels (Cantrell & Catterall, 2001). Furthermore in GT-1 cells, cyclic nucleotide gated non-selective cation channels have been described (Vitalis et al, 2000;Charles et al, 2001), which may also be related to Ca 2+ dependent currents.…”
Section: Dapmentioning
confidence: 99%